PARTISIPASI MASYARAKAT DALAM MENDUKUNG PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN KURAO PAGANG KECAMATAN NANGGALO KOTA PADANG - wahyuni fajriah; yurni suasti (JURNAL BUANA, 2020)
This study aims to determine the form of community participation in the form of energy, thoughts, goods and money in supporting the KOTAKU program in Kurao Pagang, Nanggalo District. This research is a descriptive quantitative research. The study population was the RW 8 community in the Kurao Pagang Village. Theresearch sample is the population of Kurao Pagangvillage in RT 1 and RT 2 and aged> 20 years, totaling 79 people. Data analysis technique is percentage. The results of the study are as follows: 1) Community participation in the form of personnel2) Community participation in the form of thoughts, namely giving opinions when asked/needed. 3) Community participation in the form of goods, namely providing assistance in the form of food to the people who participated in mutual assistance and 4) Community participation in the form of money, namely providing financial assistance for the activities of making fences and money given by the community is at a low nominal value of >Rp. 50.000.